PENINGKATAN BIOAVAIBILITAS PAKAN IKAN BERBASIS NABATI DENGAN AGEN FERMENTASI - Marlyn Kallau (Partner, 2018)
Integration of simple biotechnology practice into conventional feed manufacturing methods is expected to improve the quality of artificial feed. Fermentation technology can be used as an alternative way toincrease digestibility or bioavailability of artificial feed. The fermentation agent used is the starter of Lactic Acid Bacteria (LAB), Saccharomyces cerevisiae (Sc) and Rhizopus oligosporus (Ro). This experiment used Completely Randomized Design (CRD) with four treatments (F1; withoutfermentation agents, F2; BAL, F3; Sc and F4; Ro) and three replications so that the total experimental units were 12 experimental units. The variables measured included the physical and chemical quality of feed, the level of feed consumption and the growth parameters of tilapia. Fermented feed produced significant fish growth (P <0.05) even with the same feed consumption level compared with the control. Breakdown of the nutrient content as a result of the fermentation process causes a far more efficient utilization.